Mobile, handheld and affordable Near Infra-Red Spectrometry (NIRS) instruments for feed quality analysis - CGIAR Research Program on Livestock (2019)
Mobile, handheld and affordable NIRS instruments have been tested for scanning in plastic bags in the field, correlation with benchtop instrument for feed quality analysis has been demonstrated and the preferred instrument identified for take up by other users